Development and Application of Model Test System for Reconstruction and Expansion of Existing Shallow Single-Hole Tunnel into Twin-Arch Tunnel - Yanling Jia; Aohui Ouyang; Siyu Wang; Xing Liang; Bin Wang; Chang Liu; Fei Ye (Advances in Civil Engineering)
In this study, we developed a tunnel excavation model test system to investigate the deformation and mechanical response of the surrounding rocks and tunnel structure during the reconstruction and expansion of an existing shallow single-hole tunnel into a twin-arch tunnel. A model test was conducted to study the variation in the ground surface settlement characteristics, surrounding rock pressure, and internal stresses of the supporting structure and midwall during the construction process. The influence of the excavation distance on displacements and structural stress between the faces of the left and right tunnels was analysed using numerical software. A comparison between the model test results and the monitoring and measurement construction results revealed a fairly consistent ground surface settlement, indicating that the system is stable and reliable and can be widely applied to laboratory model test research on tunnel excavation. Results show that the excavation of the first tunnel had a significant effect on the stability of the surrounding rock within the distance of a single-tunnel span behind the tunnel face. When the excavation distance between the two tunnels exceeded twice the length of the single-tunnel span, its effect on the stresses and deformation of the reconstructed twin-arch tunnel was negligible.